Chenopodium album Linn.: A REVIEW ON VARIOUS PHARMACOLOGICAL ACTIVITIES - DAS, ANGANA; BORTHAKUR, MRIDUL KR. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Chenopodium album is widely distributed across the globe and is not only being used in the traditional system of medicine but also in modern medicine. Traditionally, the plant has been used as a hepatoprotective, sedative, diuretic, blood purifier, antiscorbutic laxative and as an anthelmintic against round and hookworms. It is also claimed that the leaves of this plant has a long traditional use in the treatment of digestive, peptic ulcer and hepatic disorder. A comprehensive account on various pharmacological activities like Antioxidant, Antimicrobial, Anti-diabetic, Antipruritic, Antinociceptive, Anti-inflammatory, Anthelmintic and Hepatoprotective activities of C. album reported are discussed in this review to explore its immense medicinal properties.